Detection of Sharia and Non-Sharia Stock Price Volatility Through Financial Performance and Firm Size Analysis (Comparative Study of LQ45 and JII30) - Nani, Nani; Syarifudin, Efi; Mabruroh, Ahda Inayati (AL-ARBAH: Journal of Islamic Finance and Banking, 2024)
Purpose - This research aims to estimate the magnitude of the influence of assets measured using firm size and company profits measured by financial performance on the volatility of Sharia and non-sharia stock prices. Through this research, it is hoped that investors will be able to assess the company's achievements and anticipate investment failures in the future.Method - Quantitative research using a regression analysis approach by comparing two research subjects, namely non-shariah shares LQ45 and sharia shares JII30. This data collection is complemented by library research.Result - The results obtained are that Financial Performance and Firm Size have an influence on share price volatility, in both Sharia and non-sharia stocks. In general, these two stocks found fluctuating data on Financial Performance and Firm Size, followed by rises and falls in share prices. This study is proven by theoretical results, statistical analysis results, and financial data recapitulation results.Implication - The existence of a significant relationship between these variables provides information for investors in making investment decisions, where fundamental analysis can be carried out by looking at the financial reports of the target company (issuer) without forgetting the analysis of Financial Performance and Firm Size data.Originality - Research comparing Sharia and non-sharia stock indices is still rarely done because many previous studies only focused on one index.